The Routledge Handbook of Second Language Acquisition and Speaking, 1st Edition. T. M. Derwing, M. J. Munro and R. I. Thomson - Hammer, Kate (Journal of Monolingual and Bilingual Speech, 2024)
The Routledge Handbook of Second Language Acquisition and Speaking, 1st Edition. T. M. Derwing, M. J. Munro and R. I. Thomson (2022). Routledge.